2018
DOI: 10.1167/tvst.7.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Intrasession Repeatability and Interocular Symmetry of Foveal Avascular Zone and Retinal Vessel Density in OCT Angiography

Abstract: PurposeTo measure intrasession repeatability and interocular symmetry of the foveal avascular zone area (FAZA) and superficial retinal vessel density (SRVD) using AngioVue Analytics optical coherence tomography angiography (OCTA).MethodsFifty healthy individuals were prospectively enrolled. OCTA scans (3 × 3 and 6 × 6 mm) were acquired twice in right and once in left eyes. FAZA (with and without rescaling) and SRVD for 18 regions (whole, fovea, parafovea, six parafoveal subregions, and nine square zones) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
6
39
2
Order By: Relevance
“…A change of less than 4.53% might simply be due to the measurement inaccuracy of OCTA, which is unable to reliably detect change of less than 4.53%. Our results are in a good harmony with the findings of a previous study on healthy subjects, where a CR of 4.1–4.64% for the whole scan and a CR of 4.4–4.85% for the parafoveal VD in the 3 × 3-mm OCTA images were calculated 23 , 34 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A change of less than 4.53% might simply be due to the measurement inaccuracy of OCTA, which is unable to reliably detect change of less than 4.53%. Our results are in a good harmony with the findings of a previous study on healthy subjects, where a CR of 4.1–4.64% for the whole scan and a CR of 4.4–4.85% for the parafoveal VD in the 3 × 3-mm OCTA images were calculated 23 , 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to previous studies on healthy subjects 18 , 34 , we have found that OCT angiography provides excellent intrasession and between-visit reproducibility of measurements in the same subject. In this study we demonstrated in diabetic patients that both intrasession and between-visit repeatability of OCTA measurements are comparable, however, both intrasession and between-visit CV values were higher for the foveal avascular zone area compared to CV values of the macular vessel density.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 18 20 However, as with all laterally based measurements in retinal images, individual differences in ocular magnification and axial length need to be corrected in order to accurately compare area measurements between subjects or across studies. 1 , 21 The need to measure axial length, as well as the large variation of area seen in normal individuals, 1 3 , 19 , 22 25 makes it difficult to use area as a measure to compare small changes associated with disease progression between subjects or for identifying an FAZ as “abnormal.” While these limitations are less important when assessing repeatability of OCTA during a single visit, 26 they represent important barriers to comparing data across different studies and populations.…”
mentioning
confidence: 99%
“…33 Similarly, Rabiolo et al showed that FAZ area was interchangeable across 3 × 3 mm, 6 × 6 mm, and 12 × 12 mm scan sizes using the AngioPlex, but that vessel density was highly dependent on scan size. 34 In contrast, Chen et al reported a ∼ 10% difference in FAZ area between 3 × 3 mm and 6 × 6 mm scan sizes (0.234 mm 2 and 0.259 mm 2 , respectively) 35 but nonsignificant vessel density differences when using the AngioVue. 35 In studies comparing scan size, the issue of image magnification is less critical, as we are only interested in relative differences between scan dimensions from the same device.…”
Section: Introductionmentioning
confidence: 93%